Thermal stack airflows inside the solar chimney with discrete heat sources: Reversal flow regime defined by chimney inclination and thermal Rayleigh number. (January 2021) - Ren, Xiu-Hong; Wang, Lei; Liu, Run-Zhe; Wang, Lin; Zhao, Fu-Yun
Abstract: Present work numerically and theoretically investigates the fluid flow and heat transfer in an inclined solar chimney induced by thermal buoyancy within a range of thermal Rayleigh numbers ( Ra ) and chimney inclination angles (α). Transport paths of fluid and heat were visualized by streamlines and heatlines, respectively. Backflow could be observed in the solar chimney when Ra increases beyond a certain value, and it directly paralyses the ventilation of the chimney. Numerical results further demonstrate that the larger the inclination angle α is, the smaller the corresponding critical Ra number of the reverse flow occurs at the glass side is. The larger the inclination angle α is, the greater Nusselt ( Nu ) value of the absorber wall is, while its increment rate decreases gradually with the increase of the inclination angle α, when thermal Ra is maintained. As α varies from 30° to 90°, corresponding critical Ra for reversal flows gradually decreases; furthermore, these critical values obtained by the theoretical solutions were higher than those from simulation. Volume flow rates increase positively with Ra when α is no more than 30°; however, they increase initially and then decline with Ra when α is no less than 45°. In order to enhance ventilation performance, a solar chimney flush attached with discrete heating sources on the glazing wall is proposed. The numerical results indicated that modified inclined solar chimney with discrete heating sources could enhancing its ventilation performance by preventing reverse flow occurring in the channel. Our investigations also showed that the optimal inclination angle for maximum volume flow rate heavily depends on Ra . This research could provide necessary technical support and guidance for solar energy utilization and building energy conservation through air channel in building envelopes. Highlights: Thermal buoyancy driven natural convection occurred in the inclined solar chimney. Reverse flows observed at the outlet strengthen with increasing inclination angle. Optimal inclination angle for maximum volume flow rate heavily depends upon Ra . Heat transfer rates and volume flow rates were influenced by discrete heating sources. Solar chimney with discrete heat sources could improve ventilation performance.